BONE FRACTURES IN EMERGENCY SITUATIONS. IMMOBILIZATION - Meliboyev Tavakkal (Galaxy International Interdisciplinary Research Journal, 2023)
Compiled in accordance with the curriculum adopted in higher education institutions , it is full of anatomy and physiology of the locomotor apparatus, causes and types of injuries when used in emergency situations, and methods of immobilization and splinting . You will learn about its importance in proper use of bone fracture in the plan of action for transporting it to the treatment facility . Don't panic when you get into an extreme situation and think about what to do first. We believe that this article will be very useful and helpful for our students, that is, future pedagogues and emergency responders.